Determinants of livelihood in the era of widespread access to ART. Issue 1 (2nd January 2017) - Hanass-Hancock, Jill; Misselhorn, Alison; Carpenter, Bradley; Myezwa, Hellen
ABSTRACT: We have only just begun to understand the long-term impact of living with chronic HIV on health and livelihood after a decade of widespread access to treatment in southern Africa. This paper explores health and well-being, disability, and livelihood dynamics among people living with HIV (PLHIV) in a public healthcare setting in South Africa. We undertook a cross-sectional survey among a cohort of 1042 people on ART and explored associations between socio-demographic characteristics, treatment adherence, measures of disability (functional and activity limitations), livelihood resources (capitals) and outcomes, including food security, and exposure to livelihood shocks. A range of dynamic relationships relevant for decision-makers is evident. Age, gender, and marital status all had significant associations with levels of livelihood capitals and outcomes. Those who had been on ART for longer periods of time also had significantly higher aggregate livelihood capital. This was particularly driven by social and financial capital. Livelihoods are built within specific social and health contexts. Of particular importance is that the resources drawn on to build a livelihood differ significantly between men and women, and that different forms of disability also have gender-specific pathways in influencing livelihood and livelihood outcomes. Our results support the need for a gender-sensitive approach to supporting the well-being and livelihoods of PLHIV. Of equal importance is an approach that considers more comprehensively the new experiences of comorbidities and disabilities that may occur with a long life on ART.